iOS medication assistant App - MEDAIDE - Beh, Jun Ming (2016)
In Singapore, private healthcare institutions provide 80% of the primary healthcare services and the government provides the remaining 20%. With the growing needs for better healthcare services, Singapore has launched an initiative termed “NEHR” (National Electronic Health Record) in 2011 to facilitate seamless delivery of healthcare services between government and private healthcare institutions. However, even with the NEHR initiative, the challenges of medication adherence and awareness still remain.